Studi Literatur: Peran Quick Response Code Indonesian Standard (QRIS) dalam Mendukung Integrasi Sistem Informasi Akuntansi, FinTech, dan Open Banking di Era Digitalisasi Keuangan - Agape Anjumarito Panjaitan; Lyla Riani Lumbantobing; David Efendi (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
transparency, and speed in recording financial transactions. QRIS, as the national digital payment standard, has been widely used to integrate various payment channels and encourage the automation of financial recording. This study utilises a literature review method sourced from scientific journals, official reports from financial institutions, and academic publications related to This study discusses the role of the Indonesian Standard Quick Response Code (QRIS) in supporting the integration of accounting information systems with financial technology and open banking in the era of financial digitalisation. The background of this study stems from the need for organisations and business actors to improve efficiency accounting information systems, fintech, and open banking. The results of the study show that the implementation of QRIS facilitates the integration of transactions into accounting systems in real time, reduces the risk of manual recording errors, and speeds up the reconciliation process with banking systems. Open banking support further strengthens connectivity between financial platforms through the use of application programming interfaces, making the digital financial ecosystem more inclusive and efficient. However, this study also found challenges in terms of data security, human resource readiness, and regulatory certainty, which still need to be strengthened. The conclusion of this study is that QRIS not only serves as a digital payment instrument but also as an important catalyst in the integration of accounting information systems with fintech and open banking, which ultimately supports the creation of more transparent and accountable financial governance.